Functional Diversity of Nematode on Rice Agroecosystem in Banyumas, Central Java - Mutala'liah Mutala'liah; Lafi Na'imatul Bayyinah; Rama Adi Pratama; Nur Arum Rahmawati; Dwi Mei Widhiana (Jurnal Ilmu Pertanian Indonesia, 2026)
Diversity of ecosystem components in rice agroecosystem is one of the keys to rice growing success. There was still a lack of information regarding the functional diversity of nematodes in the rice agroecosystems, hence the purpose of this study was to investigate the functional diversity of nematodes in rice ecosystems. This study was conducted by collecting samples from rice planting centers in Banyumas: Wangon, Jatilawang, Ajibarang, Rawalo, and Baturraden. Soil samples were collected randomly around rice plants at two places in each subdistrict. A total of 100 g of soil was extracted and isolated using the White-head tray technique. The observed variables were the morphological characteristics and functions of the nematode genus. The Shannon-Weiner diversity index was used to calculate the diversity (H'), evenness (E), and dominance (D) indices. The findings revealed five distinct nematode functions: omnivore-predator (Eudorylaimus), omnivore (Dorylaimus), microbial feeder and predator (Diplogaster), bacterivore (Cephalobus and Rhabditis), and herbivore (Hirschmanniella, Meloidogyne, Helicotylenchus). The most abundant genus was Eudorylaimus (32%), followed by Hirschmanniella (23%), Dorylaimus (17%), Meloidogyne 12%, Helicotylenchus (8%), Diplogaster (4%), and Rhabditis and Cephalobus (2% each). The H' index ranged from low to moderate, the E index varied from moderate to high, and D indicated that some sites were dominant. In conclusion, the diversity of nematode functions on rice agroecosystems in Banyumas was extensive, although R1 site in Rawalo district should be concerned due to Meloidogyne domination.  Keywords: biodiversity, nematodes, paddy, soil